Anthropology of Literature in the Polish Literary Studies - Zambrzycka, Marta (Pitannâ lìteraturoznavstva, 2013)
The subject of the article is a problem of anthropological theory of literature in Polish, modern literature studies. Today in the Polish literary studies there is a large number of publications based on the concept of “anthropology of literature”. Popularity, of the anthropological context of literary studies encourages some researchers to observe phenomena of “anthropological revolution in literary criticism”. Polish literary studies haven’t still created a single, coherent definition of “anthropology of literature”. Most researchers emphasize interdisciplinary and open nature “of the anthropological project of literature”. The authors note that the literary text, included in a broad cultural context can be interpreted in terms beyond the literary, as one of the cultural practices. The benefits of this study is a presentation of the most modern and current trends in the Polish literary theory. Literary increasingly turning to interdisciplinary research, as a result there is a union of the areas of cultural studies, cultural anthropology and literary theory. The article presents the concepts of the following researchers: Edward Kasperski, Grzegorz Godlewski, Ryszard Nycz, Małgorzata Czermińska, Ewa Kosowska, and others. It was tested in this study, that the term “anthropology of literature” is interpreted variously, and is not subject to a single definition. Literary researcher, Michał Paweł Markowski, says, that the phrases: “literary anthropology”, and “anthropology of literature” could mean the phenomenon quite different from each other – the differences was shown in this text. According to some researchers, the notion of “anthropology of literature” is still not the clear concept of literary analysis, but a kind of an interdisciplinary project with undefined boundaries.